2014
DOI: 10.2320/matertrans.m2014107
|View full text |Cite
|
Sign up to set email alerts
|

Selective Dissolution of Pt–Co Binary Alloys and Surface Enrichment of Platinum in Sulfuric Acid Solution

Abstract: The selective dissolution of cobalt and the consequent surface enrichment of platinum in PtCo binary alloys immersed in 0. ) exhibited more extensive selective dissolution and roughened surfaces. In this study, the selective dissolution and surface morphology of the PtCo alloys are discussed on the basis of these experimental results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Our group introduced inductively coupled plasma mass spectrometry (ICP-MS) to quantify the trivial amounts of dissolved Pt and M. 1519) PtM alloys were subjected to 100 cycles of potential cycling in a stationary solution, and the amount of dissolved Pt and M was directly quantified by analyzing the test solution using ICP-MS. Using this method, we clarified the effects of M species, 15) range of potential cycling, 16) Co composition on the dissolution mechanism of PtM alloys, 17,18) and the correlation between the dissolution of M and the morphological change of the surface. 19) However, the amount of dissolved Pt and M obtained by ICP-MS was an integrated value in the 100 cycles of potential cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Our group introduced inductively coupled plasma mass spectrometry (ICP-MS) to quantify the trivial amounts of dissolved Pt and M. 1519) PtM alloys were subjected to 100 cycles of potential cycling in a stationary solution, and the amount of dissolved Pt and M was directly quantified by analyzing the test solution using ICP-MS. Using this method, we clarified the effects of M species, 15) range of potential cycling, 16) Co composition on the dissolution mechanism of PtM alloys, 17,18) and the correlation between the dissolution of M and the morphological change of the surface. 19) However, the amount of dissolved Pt and M obtained by ICP-MS was an integrated value in the 100 cycles of potential cycling.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work suggested the dissolution model of Co-rich Pt alloys; numerous cylindrical pits uniformly distributed on the surface as a result of Co selective dissolution and Pt surface diffusion (porous Pt-enriched layer formation). 19 However, no porous structure was detected because obtaining the porous surface morphology of Pt-Co alloys is not very straightforward. No highmagnification images of Pt-Co alloys using FE-SEM could be obtained because of the magnetic property of the Pt-Co alloys.…”
Section: Gbmentioning
confidence: 99%
“…We directly measured the amount of both Pt and M dissolved from Pt-M alloys in a test solution using inductively coupled plasma-mass spectrometer (ICP-MS) under 100 cycles of potential cycling; this method was applied to various alloys, such as Pt-cobalt (Co), Pt-nickel (Ni), Pt-iron (Fe), and Pt-Cu. [16][17][18][19][20] It was confirmed that both Pt and M are dissolved from Pt-M alloys and that the amount of the dissolution of M is much higher than that of Pt. Recently, a novel system combining ICP-MS with a solution-flow system has been successfully established for the online and simultaneous detection of both Pt and M. [21][22][23][24] We also established a solution-flow electrochemical technique, known as channel flow multielectrode (CFME), for the detection of both Pt and Fe.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…1417) We have reported that both Pt and M dissolve from PtM alloys under potential cycling and that much more M dissolves than Pt. In other words, M was found to be selectively dissolved from PtM alloys, and the effects of the specific M used, 14) the potential range of the cycling, 15) and the alloy composition 16,17) on this selective dissolution behavior were investigated. Moreover, in order to clarify the dissolution behavior of PtM alloys in detail, a channel-flow multi-electrode (CFME) has been developed.…”
Section: Introductionmentioning
confidence: 99%